Three-dimensional characterization of ascending aortic strain, motion and growth in patients undergoing thoracic endovascular aortic repair - Nicasius Tjahjadi, MD; Carlos Campello Jorge, MD; Prabhvir S. Marway, MD; Taeouk Kim, MSc; Timothy Baker, PhD; Constantijn Hazenberg, MD, PhD; Joost A. van Herwaarden, MD, PhD; C. Alberto Figueroa, PhD; Himanshu J. Patel, MD; Nicholas S. Burris, MD (JVS - Vascular Science)
Objective: We utilized vascular deformation mapping (VDM) to assess ascending aortic motion, regional stiffness and growth in patients who underwent zone 2/3 thoracic endovascular aortic repair (TEVAR) to quantify changes in ascending aorta biomechanics after endograft implantation. Methods: Multi-planar, multi-directional aortic motion, aortic strain, and three-dimensional aortic growth was extracted by VDM from electrocardiography-gated computed tomography angiograms. Aortic displacement and strain were compared between patients who underwent TEVAR (both pre- and post-procedure) and in patients with dilated ascending aorta (>4.0 cm) and a non-dilated control group. Results: One hundred twenty subjects were included for analysis. Between pre-TEVAR and post-TEVAR, total displacement decreased (4.87 ± 1.52 mm vs 4.13 ± 1.43 mm; P = .03). Ascending aortic cross-sectional area strain at the sinuses (SVS), mid-ascending (MA), and proximal arch (PA) were lower in the pre-TEVAR group (SVS, 8.3% ± 4.7%; MA, 6.2% ± 3.2%; PA, 6.3% ± 3.0%; all P < .001) compared with non-dilated controls (SVS, 14.0% ± 6.6%; MA, 14.9% ± 6.6%; PA, 14.9% ± 6.9%). TEVAR increased aortic strain at the MA (pre-TEVAR, 6.2% ± 3.2%; post-TEVAR, 8.5% ± 4.6%; P < .001) and PA (pre-TEVAR, 6.3% ± 3.0%; post-TEVAR, 9.0% ± 4.6%; P < .001). A moderate, negative correlation (R = −0.57; P = .007) between MA aortic growth rate and aortic strain was observed post-TEVAR. Conclusions: Zone 2/3 TEVAR introduces changes in ascending aortic biomechanics. Patients with lower post-TEVAR strain, suggesting higher aortic stiffness, may be at highest risk of progressive growth. Imaging-based assessment of aortic biomechanics may help improve risk stratification for long-term outcomes post-TEVAR. : Clinical Relevance: Although thoracic endovascular aortic repair (TEVAR) is popular as a minimally invasive treatment for aortic aneurysm and dissection, concerns remain about unfavorable long-term cardiovascular outcomes due to stiffening and geometric changes in the native aorta. In this study, we used dynamic vascular deformation mapping, an emerging image registration technique, to assess longitudinal pulsatile ascending aortic motion and growth in TEVAR patients. Our findings reveal that ascending aortic biomechanics are often abnormal before TEVAR. Post-TEVAR, we observed decreased axial motion, increased pulsatile strain, and growth of the native ascending aorta at rates comparable to those observed in ascending aneurysm, even in patients with minimal or no ascending dilation. Ascending growth was fastest in those with lower post-TEVAR ascending aortic strain, suggesting the contribution of aortic wall stiffening.